Taxonomy and distribution of seagrasses in the Western Coast of the Gulf of Davao, Southern Philippines - Calumpong, Hilconida P; Medalla, Susan G.; Mendez, Ernani G. (1985)
Seagrasses were collected from 16 sites along the western coast of the Gulf of Davao, including Samal and Talikud Islands, in southern Philippines during February nd March 1983. Nine species in two families and six genera were recorded. Of those, seven are new Philippine distribution records.
Includes bibliographical references (pages 78-79) and index.
Keywords: Botany; Seagrasses -- Taxonomy; Seagrasses -- Distribution -- Davao, Philippines